1996
DOI: 10.2113/gsecongeo.91.2.243
|View full text |Cite
|
Sign up to set email alerts
|

Epithermal gold mineralization, Acupan, Baguio District, Philippines; geology, mineralization, alteration, and the thermochemical environment of ore deposition

Abstract: A large gold-rich adularia-sericite-style epithermal vein system formed at 0.65 Ma at Acupan, Baguio district, Philippines, during a period of high K magmatism. Low-salinity (•0.5 wt % NaC1 equiv), gassy (up to 0.41 m CO.2) meteoric fluids with temperatures of up to 300øC or more xvere focused into a series of steeply dipping interconnected faults and joints in the Virac granodiorite, Balatoc diatreme, Lucbuban gabbro, and Zig-Zag Formation. Prolonged and varied geothermal activity resulted in the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
34
0
13

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 17 publications
6
34
0
13
Order By: Relevance
“…Barnes, Το επιθερμικό σύστημα της Τήνου στο σύνολο του χαρακτηρίζεται ως χαμηλής θείωσης, (Casadevall & Ohmoto, 1977, Barnes, 1979, Henley & Ellis, 1983, Shelton et al, 1990, Zhang & Spry, 1994, White & Hedenquist, 1995, Cooke et al, 1996, Spry et al, 1996, So et al, 1997, Choi et al, 1998. Οι παρατηρήσεις που οδήγησαν στο παραπάνω συμπέρασμα είναι οι ακόλουθες:…”
Section: πίνακας 1 τιμές σταθερών γινομένου διαλυτότητας (Logkunclassified
See 3 more Smart Citations
“…Barnes, Το επιθερμικό σύστημα της Τήνου στο σύνολο του χαρακτηρίζεται ως χαμηλής θείωσης, (Casadevall & Ohmoto, 1977, Barnes, 1979, Henley & Ellis, 1983, Shelton et al, 1990, Zhang & Spry, 1994, White & Hedenquist, 1995, Cooke et al, 1996, Spry et al, 1996, So et al, 1997, Choi et al, 1998. Οι παρατηρήσεις που οδήγησαν στο παραπάνω συμπέρασμα είναι οι ακόλουθες:…”
Section: πίνακας 1 τιμές σταθερών γινομένου διαλυτότητας (Logkunclassified
“…Σφαλερίτη-Βουρτσίτη-Γκρηνοκίτη, κυ ρίως στα αρχικά στάδια απόθεσης φανερώνει χαρακτήρες επιθερμικου συστήματος υψηλής θείωσης, το οποίο μεταβαίνει συνολικά προς χαμηλής θείωσης, (Zhang & Spry, 1994, White & Hedenquist, 1995, Cooke et al, 1996.…”
Section: πίνακας 1 τιμές σταθερών γινομένου διαλυτότητας (Logkunclassified
See 2 more Smart Citations
“…Experimental studies have showed that magnesium has the capacity to increase the rate of hydrogen dissociation, slow down its adsorption kinetics, and lead hydrogen-bearing gases to condense (Swartz et al 1999). This hypothesis is supported by the presence of magnesium minerals in the most studied Ag-Au-Te ore deposits such as: dolomite-talc-brucite (Panormos Bay; Tombros et al 2004Tombros et al , 2005Tombros et al , 2007, Mg-chlorite (Acupan; Cooke et al 1996;Cooke and McPhail (2001), dolomite (Cripple Creek; Thompson et al 1985;Kelley et al 1998), dolomite and Mg-chlorite (Emperor, Tuvatu; Ahmad et al 1987;Scherbarth and Spry 2006), roscoelite and dolomite (Porgera; Richards and Kerrich 1993;Ronacher et al 2004) and Mg-chlorite and manganese ores (Sunnyside mine; Casadevall and Ohmoto 1977).…”
mentioning
confidence: 91%